Phytopharmacology of Ficus religiosa - Chandrasekar, S. B.; Bhanumathy, M.; Pawar, A. T.; Somasundaram, T. (Pharmacognosy Reviews)
Herbs have always been the principal form of medicine in India. Medicinal plants have curative properties due to the presence of various complex chemical substances of different composition, which are found as secondary plant metabolites in one or more parts of these plants. Ficus religiosa (L.), commonly known as pepal belonging to the family Moraceae, is used traditionally as antiulcer, antibacterial, antidiabetic, in the treatment of gonorrhea and skin diseases. F. religiosa is a Bo tree, which sheltered the Buddha as he divined the “Truths.” The present review aims to update information on its phytochemistry and pharmacological activities.
Keywords: Antibacterial; antidiabetic; antiulcer; ficus religiosa (L.); pharmacological activities; phytochemistry